An international, multicentre survey of -lactam antibiotic therapeutic drug monitoring practice in intensive care units - Wong, G.; Brinkman, A.; Benefield, R. J.; Carlier, M.; De Waele, J. J.; El Helali, N.; Frey, O.; Harbarth, S.; Huttner, A.; McWhinney, B.; Misset, B.; Pea, F.; et al. (Journal of antimicrobial chemotherapy, 2014)
Emerging evidence supports the use of therapeutic drug monitoring (TDM) of β-lactams for intensive care unit (ICU) patients to optimize drug exposure, although limited detail is available on how sites run this service in practice. This multicentre survey study was performed to describe the various approaches used for β-lactam TDM in ICUs. A questionnaire survey was developed to describe various aspects relating to the conduct of β-lactam TDM in an ICU setting. Data sought included: β-lactams chosen for TDM, inclusion criteria for selecting patients, blood sampling strategy, analytical methods, pharmacokinetic (PK)/pharmacodynamic (PD) targets and dose adjustment strategies. Nine ICUs were included in this survey. Respondents were either ICU or infectious disease physicians, pharmacists or clinical pharmacologists. Piperacillin (co-formulated with tazobactam) and meropenem (100% of units surveyed) were the β-lactams most commonly subject to TDM, followed by ceftazidime (78%), ceftriaxone (43%) and cefazolin (43%). Different chromatographic and microbiological methods were used for assay of β-lactam concentrations in blood and other biological fluids (e.g. CSF). There was significant variation in the PK/PD targets (100% fT>MIC up to 100% fT>4xIC) and dose adjustment strategies used by each of the sites. Large variations were found in the type of β-lactams tested, the patients selected for TDM and drug assay methods. Significant variation observed in the PK/PD targets and dose adjustment strategies used supports the need for further studies that robustly define PK/PD targets for ICU patients to ensure a greater consistency of practice for dose adjustment strategies for optimizing β-lactam dosing with TDM.